Liping Kabitenyo : talambuhay ng mga kilala at di-kilalang Kabitenyo - Calairo, Emmanuel Franco. 4 0 16; 5 (Dasmariñas, Cavite : Cavite Studies Center, Unibersidad ng de La Salle, 1999)
Biographies of known and unknown families of Cavite Province.
Hulyo 1999.
Includes bibliographical references (v. 1, p. 193-[198]) and index.
In Tagalog.
Keywords: 2 -- 0; 6; 20; Cavite Province (Philippines) -- 20 -- Biography; 2